2019
DOI: 10.1149/09202.0165ecst
|View full text |Cite
|
Sign up to set email alerts
|

Development of “Soft” Cleaning Chemistries for Enhanced STI Post-CMP Cleaning

Abstract: With the rapid miniaturization of advanced technologies, limiting device defects has become of utmost importance in maintaining high performing integrated circuits. Shallow trench isolation (STI) chemical mechanical planarization (CMP) uses a synergistic balance of ceria (CeO2) nanoparticles and functional chemistry to modulate surface adsorption interactions necessary to remove excess topography. This work aims to develop a post-CMP cleaning chemistry that enhances nanoparticle removal via “soft” encapsulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 21 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…Re-adhesion can be migrated through zeta potential adjustments 79 or use of surfactants. [80][81][82][83] Mechanisms of CNP removal with GDWs under megasonic conditions.-The mechanisms underlying the removal of CNPs from the SiO 2 film surface by GDW supply and under megasonic conditions are depicted in Fig. 13.…”
Section: Resultsmentioning
confidence: 99%
“…Re-adhesion can be migrated through zeta potential adjustments 79 or use of surfactants. [80][81][82][83] Mechanisms of CNP removal with GDWs under megasonic conditions.-The mechanisms underlying the removal of CNPs from the SiO 2 film surface by GDW supply and under megasonic conditions are depicted in Fig. 13.…”
Section: Resultsmentioning
confidence: 99%
“…Ascorbic acid, ammonium carbonate, Triton X-100 (used for cleaning Si 3 N 4 and Si 3 N 4 surfaces). 119 Graverson et al 120 developed post-CMP chemistry using a polyelectrolyte/surfactants (POS) matrix to clean the ceria nanoparticle contaminants at very low friction. 120 For the removal of contaminants, they employed the concept of charge flipping/surface adsorbing "soft" encapsulated process.…”
Section: Application-based Post-cmp Cleaningmentioning
confidence: 99%
“…119 Graverson et al 120 developed post-CMP chemistry using a polyelectrolyte/surfactants (POS) matrix to clean the ceria nanoparticle contaminants at very low friction. 120 For the removal of contaminants, they employed the concept of charge flipping/surface adsorbing "soft" encapsulated process. The other commonly noticed defect after oxide CMP is scratch.…”
Section: Application-based Post-cmp Cleaningmentioning
confidence: 99%
“…While this has shown to be an effective mode of particle removal, there is an increase in the process shear force (mechanical component), which results in secondary defect formation (i.e., increased scratching/surface roughness). , More recently attention has shifted to developing p-CMP cleaning formulations that employ encapsulation of the CeO 2 nanoparticle using supramolecular chemistries (i.e., surfactants, polyelectrolytes, liposomes, etc.). Previous work has shown that the shape and charge of the supramolecular structure play a crucial role in effective CeO 2 nanoparticle removal. More specifically, upon delivery to the wafer surface, micelles recover at a slower rate than polyelectrolytes. Though these additives do reduce the overall shear force and help to minimize defectivity induced during the cleaning process, it is not perfect and can cause p-CMP defects from the contact modality.…”
Section: Introductionmentioning
confidence: 99%